If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + 6) = -28 + 4 Reorder the terms: 4(6 + 3x) = -28 + 4 (6 * 4 + 3x * 4) = -28 + 4 (24 + 12x) = -28 + 4 Combine like terms: -28 + 4 = -24 24 + 12x = -24 Solving 24 + 12x = -24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 12x = -24 + -24 Combine like terms: 24 + -24 = 0 0 + 12x = -24 + -24 12x = -24 + -24 Combine like terms: -24 + -24 = -48 12x = -48 Divide each side by '12'. x = -4 Simplifying x = -4
| 5x^3-45x^2+70x=0 | | -4/x-1=5/(2x-1) | | 3(3x+2)=-5(4x-2)+2x | | 15/(5/9)= | | 2x+15=9x+36 | | 3x-2=8+2x | | 12-(10x)+3x-(-10)= | | 36b^2-121g^2= | | 4r^2+12rt+9t^2= | | 8x^2-10x-25= | | 4f/58 | | 23-6=x | | 7x^2+79x+22=0 | | f(pi/6)=2sin(pi/6)-cos2(pi/6) | | 8=4xq | | 15b^2-21b-72= | | 12x^2-11x-36= | | 2*sin(pi/6) | | 4x-15+2x-10=37 | | 100a^2-196= | | (x-1)(x+5)=5 | | 2x-x^2+24=0 | | 2x^3-6x^2-56x= | | 2x^2+6x-4= | | 2x^3+5x-13=0 | | x^3+3x^2-40x= | | (2x+3)=(75-2x) | | 5y-26=-6+9y | | 3(x*x)=243 | | ln(y^2+15)=ln(y+3)+ln(y) | | -x^2-11x-30= | | x^3-3x^2-54x= |